Membangun Semangat Pelayanan Calon Katekis dalam Kegiatan Rohani di Lingkungan - Hemma Gregorius Tinenti; Emilia Barek Ola (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
The research addresses the lack of active involvement of prospective catechists in spiritual activities and their lack of awareness of their primary duties. The study aims to encourage formal educational institutions to focus on educating and preparing students to become professional catechists and to increase awareness of their main tasks from an early age. The author utilized qualitative methods, including a descriptive and evaluative model, and conducted open interviews with community leaders and students at Sekolah Tinggi Pastoral Keuskupan Agung Kupang (STIPAS Keuskupan Agung Kupang). The findings revealed the inactivity and ignorance of prospective catechists about their duties. The research suggests the need for educational institutions to provide assignments and practical experience in a sustainable environment and to improve coordination between these institutions and the Church or parish.